(3cJGH TQhW GdEjeGfs - (3eMeO Hf GdbGSe Hf EHQGgje Hf ESeGYjd, , Hf Ydj Hf CHj WGdHs ((3eMeO Hf EHQGgje Hf CMeO Hf YGeQ Hf Ydi s)
(3ChdgG (B:s
(3bhd CejQ GdeDefjf Ydi ai GdEjeGf hJaSjQ Pdc heNQLg ef WQjb GdHGWf , hgh TQM HGWf GdEjeGf hceGd COH Cgd GdeYQaI HGdgd , hge GdaQbI GdfGLjI , hPcQ NUhU Gddg dge heffg Ydjge s
(3BNQgG (B:s
(3Ke EYdehG Cf JKHjJ Gddg hMHdg dGjfbWY def ESJeSc Hg hdGjPgH def JeSc Hg Edi ZjQg Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI ebGHdIs
(3cJHJ GdahGJM HGdNW GdSejc s
(3Ydi hQbJgG GdChdi JedcGJ MOjKI s
(3ef cdGe GdEeGe Ydi LeYg GdeDda hbGe HJHjVg hEjVGMg s
Keywords: (3GdJhMjO hGdedd hGdfMds